The impact of ENSO on coral heat stress in the western equatorial Pacific. (31st March 2015) - Kleypas, Joan A.; Castruccio, Frederic S.; Curchitser, Enrique N.; Mcleod, Elizabeth
Abstract The Coral Triangle encompasses an extensive region of coral reefs in the western tropical Pacific with marine resources that support millions of people. As in all other reef regions, coral reefs in the Coral Triangle have been impacted by anomalously high ocean temperature. The vast majority of bleaching observations to date have been associated with the 1998 La Niña phase of ENSO. To understand the significance of ENSO and other climatic oscillations to heat stress in the Coral Triangle, we use a 5‐km resolution Regional Ocean Model System for the Coral Triangle (CT‐ROMS) to study ocean temperature thresholds and variability for the 1960–2007 historical period. Heat‐stress events are more frequent during La Niña events, but occur under all climatic conditions, reflecting an overall warming trend since the 1970s. Mean sea surface temperature (SST) in the region increased an average of 0.1 °C per decade over the time period, but with considerable spatial variability. The spatial patterns of SST and heat stress across the Coral Triangle reflect the complex bathymetry and oceanography. The patterns did not change significantly over time or with shifts in ENSO. Several regions experienced little to no heat stress over the entire period. Of particular interest to marine conservation are regions where there are few records of coral bleaching despite the presence of significant heat stress, such as in the Banda Sea. Although this may be due to under‐reporting of bleaching events, it may also be due to physical factors such as mixing and cloudiness, or biological factors that reduce sensitivity to heat stress.